The Bound Auxins: Protection of Indole-3-acetic Acid from Peroxidase-catalyzed Oxidation - Cohen, J.D.; Bandurski, R.S.
Indole-3-acetic acid (IAA)was oxidized by horseradish peroxidase, but ester and amide conjugates of IAA were not degraded. Addition of indolea cetyl-myo - inositol, indoleacetyl-L-aspartate, indoleacetylglycine, indoleacetyl-L-alanine, indoleacetyl-D-alanine, or indoleacetyl-fi-alanine did not affect the rate of oxidation of IAA by horseradish peroxidase. Peroxidase preparations from Pisum sativum L. and Zea mays L. behaved similarly in that they rapidly oxidized IAA, but not conjugates found in the plant from which the peroxidase was prepared. These results indicate that conjugation could affect the stability of IAA in vivo.
Keywords: AUXIN (BOUND); AUXIN OXIDATION; IAA OXIDASE; PEROXIDASE; PISUM; ZEA